Prevalence of Depression and its associated factors among undergraduate students of a private university, Gurugram, Haryana - Vashist, Sunita; Gupta, Nidhi; Singla, Neha; Kataria, Priya; Narang, Sangeeta; Jha, Namrta (Indian Journal of Community Health, 2025)
Depression is a mood disorder that causes a persistent feeling of sadness and loss of interest. It is an important health issue among college students. Students are exposed to multiple factors like large workloads, time deadlines, assessments and different learning environments during their academics that have been shown to contribute to high levels of depression, anxiety, and stress. A cross-sectional study was carried out in a private university among 381 undergraduate students. A self-administered questionnaire and PHQ-9were used to collect the information on socio-demographic profile, risk factors and level of depression among the enrolled students respectively. The mean age of the study participants was 21.79+1.69years, and the majority (73%) were females. The overall prevalence of depression was 64% among participants. The high rate of depression among university students is a serious problem, and efforts should be made to raise awareness of it among both students and college administrators.